2016
DOI: 10.1308/rcsann.2016.0174
|View full text |Cite
|
Sign up to set email alerts
|

Portobiliary fistula following laparoscopic cholecystectomy

Abstract: The laparoscopic approach has replaced open surgery as the gold standard for cholecystectomy. This technique is, however, associated with a greater incidence of bile duct injuries (BDIs). We report a case of portobiliary fistula (PBF), a rare complication of BDI, occurring post laparoscopic cholecystectomy (LC). PBF has been reported after procedures such as endoscopic retrograde cholangiopancreatography and pathologies such as liver abscesses, but only once previously in the setting of LC. We discuss the mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Possible treatment strategies include medical management, balloon tamponade, coil embolization, percutaneous or transjugular stent placements, and surgical repair. 1 In addition, So et al reported a successful treatment of a portobiliary fistula with a FCSEMS. 3 In their case, the fistula, caused by a biliary stent for management of obstructive jaundice in a palliative setting in a patient diagnosed with hepatocellular carcinoma, led to recurrent bacteremia and upper gastrointestinal bleeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Possible treatment strategies include medical management, balloon tamponade, coil embolization, percutaneous or transjugular stent placements, and surgical repair. 1 In addition, So et al reported a successful treatment of a portobiliary fistula with a FCSEMS. 3 In their case, the fistula, caused by a biliary stent for management of obstructive jaundice in a palliative setting in a patient diagnosed with hepatocellular carcinoma, led to recurrent bacteremia and upper gastrointestinal bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only 2 cases of portobiliary fistulas after liver transplantation (LT) and only 6 cases related to endoscopic retrograde cholangiopancreatography (ERCP) have been reported in the literature. 1 The etiologies range from iatrogenic injuries to hepatobiliary pathologies (eg, cholangitis and stone erosion) but may also be caused by recurrent or chronic inflammatory processes and vascular pathologies. 2 To our knowledge, this is the first reported case of a portobiliary fistula in a liver transplant recipient treated with endoscopically deployed biliary fully covered self-expandable metal stent (FCSEMS).…”
Section: Introductionmentioning
confidence: 99%
“…In the case highlighted a two-year period elapsed prior to the onset of symptoms related to the porto-biliary fistula. There has been two previously documented cases of haemobilia due to a porto-biliary fistulae complicating laparoscopic cholecystectomy [12], [13].…”
Section: Discussionmentioning
confidence: 99%
“…Porto-biliary fistula is an uncommon cause of haemobilia. It is a complication after bile duct procedures and manipulation [7] . It is a rare entity and the literature on this topic is restricted to case reports [7] , [8] , [9] .…”
Section: Introductionmentioning
confidence: 99%
“…It is a complication after bile duct procedures and manipulation [7] . It is a rare entity and the literature on this topic is restricted to case reports [7] , [8] , [9] . To date, less than 30 cases have been described.…”
Section: Introductionmentioning
confidence: 99%